Calibração visando recomendações de fertilização fosfatada para as principais culturas de grãos sob sistema plantio direto no Paraguai - Andrada, Martín Maria Cubilla (2005)
At present time, 60% of the grain crop area in Paraguay is under the no-till (NT) system. This fact puts the country as a leader in this conservation practice. With the expansion of NT in the country, some questions were raised with respect to fertilizer recommendations, specially with Phosphorus (P). Those recommendations were conducted on the conventional system of soil tillage (plow + disc). The objective of this work was to conduct calibration studies in seven different locations of the Eastern Regions of Paraguay, in order to obtain phosphate fertilizer recommendations for crops such as wheat, corn and soybean under NT system. These experiments were conducted since 2003 to 2005, with soils with different texture and initial fertility levels, located on regions that were representative of the grain production area, with different records of NT adoption. In the Misiones Department, experiments were carried out in two sites (one with medium and another with high level of initial fertility, both with same texture); in the Itapúa Department, in two sites (one with high and another with low initial fertility, both with different textures); in the Department of Alto Paraná (two sites of low fertility, and with different textures); and one in the Department of Amambay, with low initial fertility. The experimental design was random blocks with split plots and three replications. The main plots received five P205 dosis (0, 50, 100, 200 and 400 kg ha-1) with the objective of building up soil fertility levels. In these plots wheat were seeded. In the split plot four P205 dosis were applied for corn and soybean crops in order to obtain the response curve. In each plot 10 soil samples at 0 to 10 cm depth were taken before seeding and right after harvest of each crop. The phosphorus source were 0-46-0 fertilizer, denominated triple super phosphate, being applied over the soil surface. The build up of P was 10 more influenced by initial level than by soil texture. In soils with low initial P level it was necessary to apply 36.5 kg P205 ha-1 to increase 1 mg dm-3 of soil P. In the soils with medium to high initial P level (with historic of fertilization) it was necessary to apply 18.6 kg P205 ha-1 to increase 1 mg dm-3 of soil P. The sufficient P level was higher than that used in Southern Brazil being the influence of texture lesser than as related by ROLAS, the sufficient P level for soils from 410 to 600 g kg-1 of clay was 12 mg dm-3 and for soils from 210 to 400 g kg-1 of clay was 15 mg dm-3. These results probably are due to two main reasons: 1) the shallow soil layer sampled (0 to 10 cm) has a higher P concentration in no-till compared to the deeper layer sampled (0 to 20 cm) in conventional tillage; 2) crops varieties used in these experiments have more yield potential, and as a result, they have higher nutrient demand as compared to older varieties used in previous experiments. In conclusion of this research, a proposal P of fertilization is recommended in NT system in Paraguay.